2014
DOI: 10.4161/cc.28897
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ability to recover from spindle disruption and loss of kinetochore spindle assembly checkpoint proteins in oocytes from aged mice

Abstract: (2014) Reduced ability to recover from spindle disruption and loss of kinetochore spindle assembly checkpoint proteins in oocytes from aged mice, Cell Cycle, 13:12, 1938Cycle, 13:12, -1947

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 74 publications
(149 reference statements)
7
45
2
Order By: Relevance
“…One suspected cause is age-related decreases in the already weak spindle checkpoint signaling in oocytes. Evidence showing decreased expression of checkpoint signaling proteins or checkpoint competence in older human and mouse oocytes is consistent with this hypothesis [69,159,160,161]. Even stronger evidence suggests that a significant contributor to the maternal age effect is compromised cohesion between sister chromatids.…”
Section: Aneuploidy In Meiosismentioning
confidence: 68%
“…One suspected cause is age-related decreases in the already weak spindle checkpoint signaling in oocytes. Evidence showing decreased expression of checkpoint signaling proteins or checkpoint competence in older human and mouse oocytes is consistent with this hypothesis [69,159,160,161]. Even stronger evidence suggests that a significant contributor to the maternal age effect is compromised cohesion between sister chromatids.…”
Section: Aneuploidy In Meiosismentioning
confidence: 68%
“…Yun et al . found that the SAC in oocytes from aged mice was more ‘permissive’, that is allowed anaphase to progress before chromosome alignment at the metaphase plate was complete, and unable to correct ‘faulty’ attachment between the kinetochores and the microtubules of the spindle; in particular, some SAC components such as mitotic arrest deficient 2 (MAD2) and aurora kinase C (AURKC) showed reduced function, especially when the oocytes were matured and handled in vitro . We propose that compromised function of the SAC may also contribute to impaired chromosome alignment and segregation in aged mares and increase the risk of aneuploidy in mature oocytes.…”
Section: Discussionmentioning
confidence: 96%
“…The mechanism underlying the increased incidence of chromosome misalignment in oocytes from aged females is unknown; however, Yun et al . suggested that dysfunction of the spindle assembly checkpoint (SAC), a mechanism involved in regulating and correcting kinetochore–microtubule attachment prior to anaphase, might play an important role in this process. Yun et al .…”
Section: Discussionmentioning
confidence: 99%
“…57). A conclusion from these studies is that functionality of the SAC with age is differently affected in different mouse strains, and not all mouse strains are equally suited to study the involvement of the SAC in the increase of missegregation events in oocytes of older mice 57 . Overall these results suggest that the SAC is functional in oocytes of older mice and still able to generate a delay in anaphase I onset, but that it becomes less efficient with age and this leads to an increase in chromosome missegregations.…”
Section: Discussionmentioning
confidence: 99%